Meykhana as one of the genres of folklore - Рзаев, Назим Агаверди оглы (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
It is known that meykhana represents which has arisen and created in the territory Baku and Absheron, an original sample of folklore. Meykhana as a whole differs from other samples of national literature radically and the ways of creation, manner of performance. Along with a variety of genres the folklore the regional originality and specificity of the environment possesses the excellent characteristic. On this property each folklore fact it is accented expresses in itself color, individual properties of a place (territory) where arose to which belongs. One main distinguishing  meykhana from other folklore samples of signs existence at it regional features is their. In this time span of expansion and an intensification of process of integration into the world culture , one of the rich sources providing independence of national and spiritual and art and esthetic consciousness is the folklore. As each genre of folklore in a context of semantics, poetic structure is caused by national intension , it is perceived as poetic model of ethnic culture and cultural wealth. It became the reason for more serious approach to collecting, studying and promotion of folklore texts in recent years.